Motivational regulations for exercise in Brazilian outpatients with bipolar disorder: An analysis based on the self-regulation theory - Fernanda Castro Monteiro; Carlos Linhares Veloso Filho; Thaís de Almeida Britto; Clara Moreira Zettel; Laíne Keisy Siqueira da Silva; Felipe Barreto Schuch; Elie Cheniaux; Thiago Sousa Matias; Lara Carneiro; Andrea Deslandes (PLoS ONE, 2026)
Despite the well-known physical activity (PA) benefits for physical and mental health, bipolar patients seem to be insufficiently active and often encounter challenges in participating in and adhering to programs involving PA. The present study aimed to assess the motivational regulation for exercise in bipolar disorder patients. This cross-sectional study utilizes objective (accelerometers) measures to assess PA. The Young Mania Rating Scale (YMRS) and the Hamilton Depression Rating Scale (HAM-D) were used to assess mania and depressive symptoms. The Behavioral Regulation in Exercise Questionnaire – 3 (BREQ-3) was used to assess the motivators for exercise. The sample was composed of 43 patients with bipolar disorder (81.5% female, mean age = 47 years; SD = 10.4). Sufficiently actives patients according to accelerometer moderate-vigorous physical activity (MVPA) were significantly more intrinsically regulated than those insufficiently actives (p = 0.002). The linear regression model showed that intrinsic regulation predicted 20% of the variability for accelerometer MVPA (p = 0.004). Notable contrasts were observed in integrated regulation. When asked whether they consider exercise as a part of their identity, 27.6% of the insufficiently active patients selected “Very true for me.” Meanwhile this view was endorsed by 57.1% of sufficiently active. Similarly, 50% of the active group reported that exercise is a fundamental part of who they are compared with 31% of the insufficiently active group. Our findings suggest that more autonomous forms of motivation, particularly integrated and intrinsic regulation, were associated with higher levels of PA among individuals with BD, whereas less active participants tended to present higher depressive symptomatology and lower motivational quality.